جينيالوجيا النقد الفلسفي في فلسفة فريدريك نيتشه - بوطورة، حنان لحبيب; منصوري، سميرة إبراهيم (جامعة وهران 2 محمد بن أحمد - مخبر الأبعاد القيمية للتحولات الفكرية والسياسية, 2023)
هدفنا في هذه الورقة البحثة إلى التعرف على جينيالوجيا النقد الفلسفي عند فريدريك نيتشه من خلال منهج وصفي تحليلي. وتوصلنا إلى نتائج منها: أن النقد الفلسفي جاء ليؤسس لمنهج جينيالوجي ثائر على كل فكرا يركن بالحياة في زاوية اللاقيمة، محاولا إعادة الاعتبار لها وللإنسان لمن خلال خلق فكر جديد لا نسقي مجاوز للفكر الميتافيزيقي وللعقلانية الصارمة، يعيد لإنسان حقوقه المسلوبة باسم الإله أو العقل، متأثرا في ذلك بجملة من الفلاسفة من بينهم: شوبنهاور، فاجنر، داروين، والذين عاد لينتقدهم وبين ما تخفيه أصول أفكارهم ويرسخ بذلك منهجه التفكيكي الثائر على كل تقليد أعمى لا يقدر قيمة الحياة ويسير بها للعدمية. Our aim in this paper is to identify the genealogy of philosophical criticism of Friedrich Nietzsche through a descriptive-analytical approach. And we reached results, including: that philosophical criticism came to establish a genealogical approach revolting against every thought that rests on life in the angle of worthlessness, trying to restore consideration for it and for the human being, through the creation of a new non-formal thought that goes beyond metaphysical thought and strict rationality, restores to man his stolen rights in the name of God or reason, influenced by In it, a group of philosophers, including: Schopenhauer, Wagner, Darwin, who returned to criticize them and what the origins of their ideas hide, thus establishing his rebellious deconstructive method on every blind tradition that does not appreciate the value of life and leads it to nihilism.
Keywords: الفلسفة النقدية -- النقد الفلسفي -- المنهج الجينيالوجي -- نيتشه، فريدريك، ت. 1900 م